Clinical efficiency of bioregulation therapy of secondary amenorrhea - Lineva O.I (LCC «Medicine-Inform», 2018)
Clinical efficiency of bioregulation therapy of secondary amenorrhea Lineva O.I. Samara State Medical University, Russia Aim: of the study was to evaluate the effectiveness of the use of multicomponent mediсines (Hormeel SN, Ovarium compositum, Klimakt-Heel) in the treatment of patients with secondary amenorrhea from the position of bioregulatory systemic medicine. Patients and Methods: 60 patients with various clinical forms of secondary amenorrhea were observed. Every patient underwent a complex clinical and laboratory examination, determination of hormonal profile, assessment of psychoemotional and vegetative status at baseline and at a 6-month interval after the treatment. The patients were divided into 3 groups. The first group included 26 women with combined uterine myoma, who received GnRH agonists for 2 months before and 4-5 months after organ-saving surgery, which led to the development of the ovarian hyperinhibition syndrome. The second group included 18 women with the resistant ovary syndrome, and the third group included 16 patients with the premature ovarian failure. Results: analyzing the effectiveness of the use of bioregulatory drugs Hormeel SN, Ovarium compositum, Klimakt-Heel in the treatment of patients suffering from secondary amenorrhea, it is necessary to emphasize their effect on the normalization  of the hormonal profile, psycho-vegetative, endocrine-metabolic, emotional and motivational clinical symptoms of the disease.  In addition to improving overall health and normalizing menstrual function in 43 (71%) of 60 patients with secondary amenorrhea, 14 patients (23.3%) had the desired pregnancy after the treatment. Conclusion: the results obtained during the study prove the use of bioregulatory drugs Hormeel SN, Ovarium compositum, Klimakt-Heel in accordance with the principles of bioregulatory medicine as an effective method for correcting menstrual dysfunction in patients with secondary amenorrhea. Our data confirm, that the bioregulatory approach recovers the processes of activation, detoxification and self-regulation of the organism by the use of ultra-small doses. Key words: secondary amenorrhea, bioregulatory medicine, Hormeel SN, Ovarium compositum, Klimakt-Heel. For citation: Lineva O.I. Clinical efficiency of bioregulation therapy of secondary amenorrhea // RMJ. 2018. № 5(I). P. 23-28.